Efficient Software Implementations of Fantomas - Cruz, Rafael J.; Aranha, Diego F. (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2016)
We present a series of software implementations of the Fantomas block cipher in resource-constrained ARM devices like the Cortex-M3 and Cortex-M4; and more powerful processors such as the ARM Cortex-A15 and modern Intel platforms. Our implementations span a broad range of characteristics: 32-bit and 64-bit versions, side-channel resistant and vectorized code for NEON and SSE instructions. Our implementations of the algorithm improve the state of the art substantially, both in terms of efficiency or compactness, by making use of novel algorithmic techniques and features specific to the target platform. In particular, our unprotected 32-bit implementation achieves speedups from 35% to 66% in the ARM Cortex-M architecture, while consuming considerably less code size. The vectorized implementations improve performance over the state of the art by 40% in the ARM Cortex-A15 and 50% in the Core i7 Ivy Bridge, setting new speed records for the implementation of the block cipher.